Educação do Campo no semiárido como política pública: um desafio à articulação local dos movimentos sociais - Menezes, Ana Célia Silva (2017)
The study deals with Field Education in the Semi-Arid as Public Policy, highlighting the role of Popular Social Movements in guaranteeing the right and articulation of this policy (s) with the Contextualized Education proposal for Living with the Brazilian Semi-Arid. The question of the existing elements in the municipal scope that affect the process of implementation of the policies of Education of the Field and which the articulations of these policies with the proposal of Contextualized Education for Living with the Semi-Arid is constituted as the problem question of investigation. From this question The general objective of the work emerges: to understand the existing elements at the municipal level that affect the process of implementing the public policies of Field Education in the Semi-Arid and the articulations of these policies with the proposal of Education contextualized in the perspective of the Coexistence with the Brazilian Semi-Arid. The work results from a field research, qualitative oriented under the theoretical-methodological principles of dialectical historical materialism,represented particularly by Gramscian thought in regard to the concept of State, Politics and Hegemony (Gramsci, 1978, 1982). It is based on the studies of Horácio Martins de Carvalho (2005, 2009), Bernardo Mançano Fernandes (2013), José de Souza Martins (1986, 1975), Ariovaldo Umbelino de Oliveira (2001, 2013) and Roseli Salete Caldart 2004), to discuss the concept of Field Education articulated to the history of the peasantry in Brazil and its protagonism in the struggles for the guarantee of rights, including the right to Education. For the discussion on Contextualized Education to Coexist with the Brazilian Semi-Arid, the studies of Adelaide Pereira da Silva (2011), Maria do Socorro Silva (2006, 2009, 2015), Maria do Socorro Silva and Adelaide Pereira da Silva (2013) ), Edmerson dos Santos Reis (2004, 2011) and Josemar da Silva Martins (2004a, 2004b, 2011). Antônio Munarim (2011) and Miguel Gonzalez Arroyo and Bernardo Mançano Fernandes (1999) contribute to the reflection on Field Education in the public policy scenario. The notion of social movements, state and politics, which appear as concepts of relevant epistemological weight in the construction of the theme, had as main interlocutors Maria da Gloria Gohn (1997, 2010) and Ilse Scherer-Warren (1996). In these authors we have as basic reference the discussion about conception and practices of social movements from the Latin American paradigm and the debate about movements in network. The research points out the partnership of the public power with the popular movements and organizations, as one of the main elements that contribute to the process of making Field Education a public public policy and brings a theoretical and scientific support to the thesis that the Campo are based on a link between the public power, the popular social movements and organizations of the countryside, and in the Semi-Arid, these policies strengthen the proposal of Contextualized Education for Coexistence with the Semi-Arid.